MENINGKATKAN PENGUASAAN KOSA KATA BAHASA INGGRIS SISWA SMP MELALUI PEMBELAJARAN BERBASIS PROYEK TIKTOK - Susiana Kaban; Vitri Rokhima (Institut Pendidikan Tapanuli Selatan, 2026)
Vocabulary mastery is a fundamental component of English language learning, as it underpins students' ability to comprehend and utilize the language effectively. However, low vocabulary mastery remains a persistent challenge, often stemming from teacher-centered instruction that lacks authentic learning experiences. This study aims to analyze the effectiveness of implementing TikTok-Project Based Learning (TikTok-PjBL) in enhancing the vocabulary mastery of seventh-grade students at SMP Swasta F. Tandean Tebing Tinggi. Utilizing a quasi-experimental method with a non-equivalent control group design, the study involved a sample of 60 students divided into two groups: an experimental class of 30 students who engaged in Project-Based Learning through TikTok video creation, and a control class of 30 students who received Problem-Based Learning (PBL). Data were collected using vocabulary mastery tests at the pre-test and post-test stages, and subsequently analyzed using descriptive statistics, paired-sample t-tests, independent-samples t-tests, and effect size analysis. The results indicated that the mean score of the experimental group increased significantly from 56.07 to 84.87. The paired-sample t-test revealed a significant difference (p < 0.001), while a Cohen’s d value of 7.118 indicated a very large effect size. These findings demonstrate that TikTok-Project Based Learning is highly effective in improving English vocabulary mastery by fostering active, collaborative, creative, and contextual learning experiences.